What is the Success Required in Digital Public Services Transformation (Case of Digital Payment for Public Apartment Rent in Semarang Regency) - Pangarso, Agung; Pebrianto, Niko (TERRACE: JOURNAL OF ARCHITECTURE & URBAN STUDIES, 2025)
Digital transformation in the public services by the local government will improve the service related to several benefits. E-public services to the people or users will become more efficient, e-public services open 24/7, reduce the administrative burden, be more transparent and accountable, and finally, digital public services help governments meet public expectations. The Public Work Agency of Semarang Regency manages affordable public apartments (flats), particularly for low-income people. There are four-storey flats in Ungaran, Ambarawa, and Pringapus with a total of 326 rooms. The management unit is facing problems related to rent payments by monthly cash (manual) transactions. The Government of Semarang Regency committed to transforming all transactions from manual to digital (e-transaction) including for public apartment rent. This study aims to answer the question: what is the success required in digital payment for public apartment rent in Semarang Regency? From the process of digital transformation in e-payment for public flat rental during the preparation stage to operations (June to September 2024), this research concluded the success required in digital payment as follows: (a) In terms of support, the political will from local leaders, adequate regulations, and commitment toward successful digital transformation become a strong foundation for supporting the preparation and implementation of the e-government project; (b) In term of capacity, the adequate ICT infrastructure both hardware and software and human resources with competences related to the e-government project. (c) In terms of value, e-government projects need to build the value of benefits for the people as users and demand side of government services. e-government projects should provide significant benefits to the people, so the project has the potential to be successful.